Unmaking the nation : the politics of identity and history in modern Sri Lanka - Jeganathan, Pradeep; Jeganathan, Pradeep; Ismail, Qadri; Social Scientists' Association of Sri Lanka (Colombo : Social Scientists' Association, 1995)
Contributed articles focusing mainly on the post-independence political scene in Sri Lanka within the broad framework of nationalism existing among the various ethnic groups during the period.
Keywords: Nationalism -- Sri Lanka; Sri Lanka -- Politics and government -- 1948-; Sri Lanka -- Ethnic relations